Internal Stakeholder Engagement, Organizational Support, Project Team EZcacy and Project Success. A Case Study of USAID aided Projects in Uganda - Kanyesige, Brenda (Student's Journal of Health Research Africa, 2021)
This study examined the relationship between internal stakeholder engagement, organizational support, project team efficacy, and project success among USAID projects in Uganda. The objectives were: to examine the relationship between internal stakeholder engagement and project team efficacy; organizational support and project team efficacy; project team efficacy and project success; and to examine the mediating effect of project team efficacy. The study applied a cross-sectional research design with a quantitative research approach. A sample of 44 projects was obtained by simple random sampling from a total of 50 ongoing projects. Data was collected using a structured questionnaire. The validity of the instrument was determined by expert judgment and Cronbach Alpha for reliability. Data were analyzed using SPSS v.25 to obtain frequencies, descriptive statistics, factor analysis, and inferential statistics in data presentation and interpretation. Findings established a positive relationship between stakeholder engagement and project team efficacy. The findings also found a positive relationship between organizational support and project team efficacy. There was a positive relationship between project team efficacy and project success. More so, findings obtained that project efficacy is a significant mediator in the relationship between organizational support and project success, but not significant in mediating the relationship between internal stakeholder engagement and project success. The findings further observed that the best predictor of project success is project team efficacy. Internal stakeholder engagement, organizational support, and project team efficacy are critical in project success. As far as project success is concerned, the factors take center stage. Moreover, project managers should concentrate most on project team efficacy.